2022
DOI: 10.3389/fimmu.2022.839945
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Dysregulation of Survivin-Targeting microRNAs in Autoimmune Diseases: New Perspectives for Novel Therapies

Abstract: It has been well established that the etiopathogenesis of diverse autoimmune diseases is rooted in the autoreactive immune cells’ excessively proliferative state and impaired apoptotic machinery. Survivin is an anti-apoptotic and mitotic factor that has sparked a considerable research interest in this field. Survivin overexpression has been shown to contribute significantly to the development of autoimmune diseases via autoreactive immune cell overproliferation and apoptotic dysregulation. Several microRNAs (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 121 publications
(133 reference statements)
0
13
0
1
Order By: Relevance
“…They revealed that miR-34a delivered by GC4-targeted nanoparticles significantly reduced tumor load in the lung and downregulated expression of survivin in the metastatic tumor [227]. Survivin, an antiapoptotic factor that has been identified as a therapeutic target in a variety of disorders, plays a crucial part in mechanisms that promote tumor development and angiogenesis [228]. HIF1α stability in low oxygen environments and/or through ROS generation enhances survivin and VEGF expression and angiogenesis [229,230].…”
Section: Lipid-based Vectorsmentioning
confidence: 99%
“…They revealed that miR-34a delivered by GC4-targeted nanoparticles significantly reduced tumor load in the lung and downregulated expression of survivin in the metastatic tumor [227]. Survivin, an antiapoptotic factor that has been identified as a therapeutic target in a variety of disorders, plays a crucial part in mechanisms that promote tumor development and angiogenesis [228]. HIF1α stability in low oxygen environments and/or through ROS generation enhances survivin and VEGF expression and angiogenesis [229,230].…”
Section: Lipid-based Vectorsmentioning
confidence: 99%
“… 40 Just recently, several microRNAs have been implicated in survivin regulation which may downregulate anti-apoptotic survivin expression in apoptotic cells or, in opposite direction, contribute to survivin upregulation, enhancing their sustained activation and autoreactivity in autoreactive immune cells. 42 …”
Section: Discussionmentioning
confidence: 99%
“…Their results revealed that cells and tumors have increased expression of survivin and cell surface proteins which provide effective OV entry and replication in DIPG cells and result in more prolonged survival [ 179 ]. To elaborate, survivin is an anti-apoptotic factor that facilitates the viability and survival of cells and has been identified as a target in the treatment of several autoimmune diseases and cancers [ 180 , 181 ].…”
Section: Msc-based Delivery Of Oncolytic Adenovirus (Oads)mentioning
confidence: 99%